Novel Non-rodent Models of Kidney Disease - Hentschel, Dirk M.; Bonventre, Joseph V. (Current Molecular Medicine, 2005)
Kidney disease in the 21st century affects increasing numbers of individuals. We continue to be challenged by our lack of understanding of the pathophysiology of acute and chronic renal disease including genetic diseases involving the kidney. Rodent knockout animals or inbred strains have greatly contributed to our understanding of many monogenetic and complex diseases. Non-rodent animal models of disease have become more attractive since genomic data has become available for a variety of organisms that offer distinct advantages over mice and rats for ease in conducting highthroughput chemical or mutagenesis screens. It is thus timely to examine the physiology and pathophysiology of the kidney or kidney equivalents in these organisms to evaluate their relevance as models for human disease. In addition to organisms whose small size and accessibility facilitate large scale screening approaches, larger animals at the other end of the spectrum offer unique physiological advantages in both size equivalency to humans as well as, in some cases, physiological and pathophysiological responses that closely mimic those of humans. Here we review a selected number of non-rodent experimental models of kidney diseases, focusing on recent advances in the use of the worm Caenorhabditis elegans, the fruitfly Drosophila melanogaster, the zebrafish Danio rerio, the little skate Leucoraja erinacea, the MGH miniature swine, merino cross sheep, and the cow Bos taurus to study kidney disease.
Keywords: acute renal failure